Stem Cell Organoid Engineering - Yin, Xiaolei (Cell Stem Cell, 2016)
Organoid systems leverage the self-organizing properties of stem cells to create diverse multi-cellular tissue proxies. Most organoid models only represent single or partial components of a tissue, and it is often difficult to control the cell type, organization, and cell-cell/cell-matrix interactions within these systems. Herein, we discuss basic approaches to generate stem cell-based organoids, their advantages and limitations, and how bioengineering strategies can be used to steer the cell composition and their 3D organization within organoids to further enhance their utility in research and therapies.